If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(3 + -6d) = (2d + -2) (3 * -4 + -6d * -4) = (2d + -2) (-12 + 24d) = (2d + -2) Reorder the terms: -12 + 24d = (-2 + 2d) Remove parenthesis around (-2 + 2d) -12 + 24d = -2 + 2d Solving -12 + 24d = -2 + 2d Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-2d' to each side of the equation. -12 + 24d + -2d = -2 + 2d + -2d Combine like terms: 24d + -2d = 22d -12 + 22d = -2 + 2d + -2d Combine like terms: 2d + -2d = 0 -12 + 22d = -2 + 0 -12 + 22d = -2 Add '12' to each side of the equation. -12 + 12 + 22d = -2 + 12 Combine like terms: -12 + 12 = 0 0 + 22d = -2 + 12 22d = -2 + 12 Combine like terms: -2 + 12 = 10 22d = 10 Divide each side by '22'. d = 0.4545454545 Simplifying d = 0.4545454545
| 64=4w | | y=.5(-10) | | x*z= | | (8k/(k-3))+1=((6k-2)/(k^2-4k+3)) | | 12x+2y=-6 | | -6n+19=-5n-1 | | -9=-y+6 | | x-3/7x-21 | | (7/x)=(21/24) | | 2x=360/4 | | 9=-y+6 | | (5/4)=(x/16) | | x=-0+6 | | 0=-y+6 | | y=21-5 | | 0.3x+5=6.5 | | 5=-6x | | 3*x-8=96 | | .02(3-(-6))-.04(-6+2)= | | 1/5/7/10 | | -6x(3x-4)=4x-2(x+2) | | 5x+2y=49.30 | | -3-2y=-5 | | 3(7-n)=-3(n-9) | | x-2(-4)=-5 | | 2(0)+y=2 | | 12-8x=86-22x | | -4x-9y-5=0 | | -6=.5x-3 | | -4x-8y=7 | | 4y-3x=2 | | 5y-3=y/2 |